A critical study on the influence of steel fiber on performance of fresh and hard self compacting concrete - Vijaykumar, H.; Shamu, Sakey (Journal of Structural Engineering, 2025)
The self compacting concrete due to its excellent deformable and segregation resistance property is essential in formwork with heavy and congested reinforcement. Fibers are added to enhance its ductility, toughness and to reduce drying shrinkage. To use this mix in the same circumstances, it should satisfy the EFNARC guidelines for the workability at fresh state and strength requirement at hardened state. The volume and length of steel fibers combined with coarse aggregates in the mix influences the flow properties of wet mix. To identify this, fibers of different lengths are added in varying dosages from 1% to 0.50% by volume of the mix in decreasing order in plain mix designed by Nan-Su method for strength of 50MPa using suitable parameters suggested, later modified it with extra cement. As steel fibers are straight and needs energy to bend, due to the influence of maximum fiber factor and maximum size of aggregate, unacceptable results for workability of fresh mix due to a phenomenon such as blockage of the spaces through the vertical bars of U-box and L-boxes are predicted. So, to reduce this, the paper recommends the fibers of length and dosage not more than 25mm and 0.60% by volume of mix respectively. Then the fresh mix satisfies the EFNARC workability requirements. The 7 and 28 days cube strength increases marginally by 2.38% and 4.47% respectively.